Analysis model of coal consumption deviation for main operation parameters in boilers burning pulverized coal and BFG. (October 2018) - Ye, Y L; Wang, H M; An, X; Jiang, W H
Abstract: For the boiler main operation parameters, the deviation of operating parameters from the target value can cause the decrease of boiler thermal efficiency, which can further lead to the increase of unit coal consumption for power generation. Aimed at this problem, the key points of the thermal efficiency calculation for boilers mixedly burning pulverized coal and blast furnace gas (BFG) were analyzed, and the coal consumption deviation analysis model was proposed based on the modified calculation formulas. This model can provide further guidance for bolier optimized operation. A 220t/h boiler was analysed as an example, which the extra coal consumption was obtained caused by the non-optimal operation parameters.